IMPLEMENTASI KEBIJAKAN HUTAN TANAMAN RAKYAT DI KABUPATEN BULUNGAN, KALIMANTAN TIMUR - Iskandar . (Jurnal Paradigma (JP), 2017)
To overcome deforrestration problem especially in production, Indonesian government try to involve society in managing the forest through Hutan Tanaman Rakyat program year 2007. The result show that implementation of HTR in Bulungan was very slow, it because the lack of understanding of society and socialization. In addition, field operator did not understand the way how to involve the people to develop it.